Banks' Net Interest Margin and the Level of Interest Rates - Ramona Busch; Christoph Memmel (Credit and Capital Markets – Kredit und Kapital, 2017)
The prevailing view in the literature is that, in the long run, an increase in the level of interest rates will impact positively on banks' net interest margins. Using a time series of more than 40 years for the German banking system, we confirm this effect (the net interest margin increases by 7 basis points for every 100 basis point increase in the interest rate level). What is more, we show that the opposite effect exists in the short run. In addition, we analyze the consequences of the low-interest-rate environment and find that banks' interest margins on retail deposits, especially term deposits, have declined by up to 97 basis points. – – Die Zinsspanne der Banken und das Zinsniveau Die vorherrschende Ansicht in der Literatur ist, dass sich langfristig ein Anstieg des Zinsniveaus positiv auf die Zinsspanne der Banken auswirkt. In dem Papier nutzen wir Zeitreihen des deutschen Bankensystems für einen Zeitraum von mehr als 40 Jahren und bestätigen den Effekt (die Zinsspanne nimmt um 7 Basispunkte zu je Anstieg des Zinsniveaus um 100 Basispunkte). Unser Hauptbeitrag ist, zu zeigen, dass es in der kurzen Frist den gegenteiligen Effekt gibt. Au???erdem untersuchen wir die Auswirkungen des Niedrigzinsumfelds und finden, dass sich die Zinsmarge der Banken auf Kundeneinlagen, besonders auf Termingeld, um bis zu 97 Basispunkte verringert hat.
Keywords: G21; 330; Net interest margin; level of interest rates